DESAIN PEMBELAJARAN DENGAN MENGGUNAKAN SITUS BERSEJARAH DALAM PAI - Abbas, Abd Rahman (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2016)
The learning activities is a series of activities and interaction between students and teachers that are controlled through planning based on the achievement of learning and teaching. Implementation of the learning process needs to be done systematically based on instructional procedures that have been developed and specified in the plan. Therefore, to understand and implement the procedure of learning in group learning, individual very urgent to be understood and developed.In general stages into three stages of learning as early learning activities, the core activities of learning and teaching activities end. Therefore, the learning process needs to be pursued through a systematic procedure and systemic. The learning procedure is a sequential process in shaping the students' ability in accordance with its intended purpose. Lesson study can be conducted in three phases, namely the level of planning, executing level and extent reflect a sustainable manner. But it will all be meaningless if it is not supported by their media appropriate learning and support to these activities, instructional media design can be adapted to the needs, because it is so closely related to the method used. In the context of PAI, historic sites so need to be used, because the presence of the PAI is inseparable from the history and civilization of Muslims, so the design of learning development will be very urgent and essential if learning PAI juxtaposed with the historic sites.